Swallowing in the first year after chemoradiotherapy for head and neck cancer: Clinician‐and patient‐reported outcomes. Issue 3 (18th June 2013) - Patterson, Joanne M.; McColl, Elaine; Carding, Paul N.; Hildreth, Anthony J.; Kelly, Charles; Wilson, Janet A.
<x xml:space="preserve">Abstract</x> Background This prospective study evaluated swallowing outcomes prechemoradiotherapy (pre‐CRT) up to 1 year post‐CRT, in a substantial cohort of patients with head and neck cancer and explored factors predicting outcome. Methods One hundred twelve patients were assessed pretreatment and at 3, 6, and 12 months posttreatment using a questionnaire, endoscopic assessment, water swallow test, and diet score. Results Seventy‐one patients were retained, the majority had oropharyngeal (53%) or hypopharyngeal cancer (20%). A marked deterioration occurred between pretreatment and 3 months posttreatment (p ≤ .01). Significant improvement between 3 and 12 months was found on 2 swallowing measures, but not self reported. Three of the 4 pretreatment assessments predicted outcomes at 1 year. Conclusion CRT results in a marked deterioration on different paradigms of swallowing measurements. Improvement occurs on some clinical measures, but limited change is observed in patients' perceptions. Pretreatment measures are important indicators of long‐term dysphagia. Swallowing recovery is complex, taking different courses between clinical tests and perspectives. © 2013 Wiley Periodicals, Inc. Head Neck36: 352–358, 2014